Evaluation of the yield and the physical and chemical changes of a soil in a step slope cultivated with maize and beans, with different life covers in a forest plantation - Alberty Rodríguez, Rafael A. (1977)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- UCR, San José (Costa Rica), 1977